Exploiting cognitive linguistics in argumentative texts didactics case of the first years of hate school common core of literature - RDJEM, Samira (Journal of Human Sciences, 2020)
This research presents a study on the importance of the application of cognitive linguistics in the teaching of the pilgrim text in the first year common core literature.Where cognitive linguistics is a modern linguistic approach that is concerned with the study of mental processes prior to verbal achievement, It calls for linking linguistic study with all cognitive mechanisms related to the production of language, and therefore can be used in the teaching of pilgrim text, whose learning depends largely on the mental competence of the learner, Learners must be given intellectual pilgrim competencies in addition to language competencies, so that they have a pilgrim textual competence by which they are able to receive and understand pilgrim texts and then produced properly.